(untitled) (SCHOLARS: Journal of Arts & Humanities, 2026)
This article explores the representation of Rashid Khalifa’s coma in Salman Rushdie’s Luka and the Fire of Life (2010) through the lens of medical realism, situating it within the broader framework of magical realism. It examines a paradoxical intersection of medical rationalism and mythic imagination in human condition. The narrative centers on a moment in which Rashid Khalifa falls into a deep sleep, resembling coma. Doctors who attend Rashid embody the limitations of conventional medical practice: managing only a drip, monitoring heartbeat, and providing little or no narrative or diagnostic clarity. It reveals the constraints of conventional medicine and the absence of narrative understanding. Rashid receives minimal medical intervention but later revives through Luka’s ‘Fire of Life.’ Rashid’s final revival through the magical Fire of Life dramatizes the tension between clinical science and mythopoetic imagination. Drawing on Rita Charon’s principles of narrative medicine, this article argues that Rushdie covertly critiques the lack of narrative competence in medical encounters and highlights the therapeutic worth of the story. The references to coma, altered consciousness, and post-recovery dream resonate with medical literature on disorders of consciousness and near-death experiences. Integrating insights primarily from Allan H. Ropper’s concept of neurology, Rita Charon’s concept of narrative medicine, and Lois Parkinson Zamora and Wendy B. Faris’s idea of magical realism, this article reveals how the novel constructs a hybrid discourse that questions and expands the limits of medical realism, situated under magical realism.